Triple-layered central pattern generator-based controller for 3D locomotion control of snake-like robots. (13th November 2017) - Qiao, Guifang; Zhang, Ying; Wen, Xiulan; Wei, Zhong; Cui, Junyu
Due to the great adaptability, snake-like robots can serve as special intelligent service robots. In this article, a novel triple-layered central pattern generator (CPG)-based controller is proposed to control the 3D locomotion of snake-like robots. The proposed triple-layered CPG includes a rhythm generation layer, a pattern generation layer, and a motoneuron layer. The nonlinear Kuramoto oscillator and the rhythmic dynamic movement primitive are, respectively, used to model the interneurons and motoneurons. The triple-layered CPG can flexibly generate the multidimensional phase-coordinated control signals of snake-like robots. Firstly, the architecture of the proposed triple-layered CPG is validated, and the impacts of control parameters on the outputs are numerically analyzed. Secondly, the smooth locomotion transition process of the triple-layered CPG is discussed. Finally, the performances of the proposed triple-layered CPG for controlling snake-like robots have been evaluated through the co-simulation of Simulink and MSC Adams [version 2012]. The results illustrate that the proposed triple-layered CPG can easily and flexibly generate continuous and smooth for controlling 3D locomotion of snake-like robots. It can improve the mobility and adaptability of snake-like robots.